Principal Component and Diversity Metrics on Biochemical, Yield and its Attributing Traits of Oat Genotypes - Bhoomika,; Arya, Satyawan; Panchata, Ravish; Neeraj, K.; Bhuker, Axay; Sachin,; Langaya, Sonu (International Journal of Bio-resource and Stress Management, 2026)
The present study was conducted during rabi November–February, 2022 at Forage Research Area, Department of Genetics and Plant Breeding, CCS Haryana Agricultural University, Hisar, Haryana, India to to assess the genetic diversity and variability among different oat genotypes. Fifty (50) elite Oat genotypes was grown were grown with three replications in a randomised block design (RBD). The 16 morpho-physiological and biochemical observations were recorded in five randomly selected plants of each genotype across all three replications and the data were analysed. The diverse genotypes were clustered into six groups. Higher inter-cluster distances as compared to intra-cluster distances indicated greater homogeneity within clusters and cluster I exhibited the highest intra-cluster distance. Maximum inter-cluster distances were observed between clusters I and II, whereas the smallest distance was between clusters II and IV. Crosses among genotypes from Clusters I and II likely to produce novel recombinants due to the high degree of divergence. Six principal components (PCs) had eigenvalues greater than one, contributing to 72.61% of the variability. From the PCA and cluster analysis it was inferred that the genotypes RO 19, HFO 1123, PLP-27, HFO 806, HFO 1222 and HFO 1003 could be used for green fodder yield, whereas UPO-20-3, HFO-1003, HFO 806 for seed yield plant-1.